Phytoextract-mediated Cupper nanoparticles via Acacia saligna: synthesis, characterization and in vitro anticancer and apoptosis inducing effects - Fuad O. Abdullah (Bioresources and Bioprocessing)
Abstract Copper oxide nanoparticles (CuO NPs) have been utilized in various applications over the past few decades. This investigates the anti-cancer and apoptosis-inducing effects of green synthesis of copper oxide nanoparticles mediated by using Acacia saligna flower extract. The flower extract was mixed with a solution of copper sulphate pentahydrate (CuSO4·5H2O) and sodium hydroxide (NaOH) as a catalyst. UV-Vis spectroscopy, FTIR (Fourier Transform Infrared Spectroscopy), XRD (X-ray Diffraction), and SEM (Scanning electron microscope), EDS (Energy Dispersive Spectroscopy) and TEM (Transmission Electron Microscopy) analysis were conducted to characterize the synthesized CuO NPs. The average particle size of the NPs was found to be 8.488 nm. Additionally, the CuO NPs exhibited noteworthy anticancer activity against the MCF-7, PC3, HT-29, and U-87MG cell lines (18.11 ± 25, 8.92 ± 0.73, 19.48 ± 0.24, and 26.08 ± 0.57, respectively). In particular, the CuO NPs demonstrated a significant effect on the human colorectal adenocarcinoma cell line (HT-29) with an IC50 value of 19.48 ± 0.24 µg/mL, surpassing that of the standard (Cis-platin, 22.20 ± 0.72). The CuO NPs also induced apoptotic-mediated programmed cell death in cancer cell lines. In conclude, this investigation suggests that green-synthesized CuO NPs with Acacia saligna flower extract could serve as a viable alternative for anticancer applications in biomedicine. However, further research is needed to understand the detailed mechanisms of action and evaluate their in vivo efficacy to better establish their potential for clinical applications.